Strength Properties of Porous Concrete Pavement Blended with Nano Black Rice Husk Ash - Putra Jaya, Ramadhansyah; K. A., Masri; S. A., Mangi; M. I., Mohd Yusak; M. R., Hainin; Muhammad Naqiuddin, Mohd Warid; Nordiana, Mashros; Haryati, Yaacob; W. I., Mohd Haziman (IOP Publishing, 2020)
In order to improve the porous concrete pavement strength, one of the elements in the porous concrete structure that needs to be considered is the cement paste binder. This study aimed to evaluate the strength properties of porous concrete pavement blended with nanoparticle from black rice husk ash (BRHA). The performance was evaluated based on compressive strength, density, age of curing and strength activity index. Four nano BRHA replacement levels were considered in the study, i.e. 10%, 20%, 30%, and 40% by weight of cement. Test results showed that porous concrete pavement containing 10% nano BRHA replacement levels exhibits excellent compressive strength and strength activity index. The results also indicate that there is no significant correlation between density of the porous concrete pavement and compressive strength.